Penatalaksanaan Oral Lichen Planus et causa Stres Psikologis - Nova Fitri, Andrian; Syafiqa Amelia, Dinda (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background : Lichen Planus is an autoimmune condition suspected to be an abnormal T-cell immune response targeting the basal epithelium, which is perceived as a foreign body. This leads to alterations in the cell surface and results in persistent inflammation. Clinically, it commonly presents in six forms: reticular (Wickham’s striae), erosive, atrophic, plaque-like, papular, or bullous lesions. The etiology of Oral Lichen Planus (OLP) remains unknown; however, several predisposing factors are believed to be associated with its manifestation, including immunodeficiency, allergies, psychological stress, mucosal trauma, genetic predisposition, and adverse drug reactions.Objective: To inform the patient about the lesion on the buccal mucosa and to determine an appropriate treatment plan. Case Report: A 62-year-old male patient come to RSGM-P Faculty of Dentistry, Universitas Trisakti, with complaints of reddish-white patches on the inner cheeks (both left and right) accompanied by pain. Conclusion: The diagnosis was established based on patient history and clinical examination, identifying Oral Lichen Planus triggered by psychological stress. Management included symptomatic therapy with corticosteroid (prednisone), along with communication, instruction, and patient education.